2023
DOI: 10.1002/ohn.354
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Underpinnings and Audiological Characteristics in Children With Unilateral Sensorineural Hearing Loss

Abstract: ObjectiveUnilateral sensorineural hearing loss (USNHL) is a condition commonly encountered in otolaryngology clinics. However, its molecular pathogenesis remains unclear. This study aimed to investigate the genetic underpinnings of childhood USNHL and analyze the associated audiological features.Study DesignRetrospective analysis of a prospectively recruited cohort.SettingTertiary referral center.MethodsWe enrolled 38 children with USNHL between January 1, 2018, and December 31, 2021, and performed physical, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In two out of five children, the etiology of USNHL remained unknown, which is consistent with what has been reported by other studies in the literature [ 29 , 30 ] and makes it difficult to predict the long-term hearing outcomes of these patients. Possible undetected causes of USNHL in the pediatric population might be attributable to genetic variants of unknown/uncertain significance, undiagnosed congenital cytomegalovirus infection (as most cases are asymptomatic at birth), or asymptomatic/paucisymptomatic postnatal infections [ 5 , 10 , 12 ]. This study showed that the characteristics of UNSHL are highly variable regarding age at diagnosis, affected side, degree, hearing changes over time, audiometric configuration, and use of a hearing device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two out of five children, the etiology of USNHL remained unknown, which is consistent with what has been reported by other studies in the literature [ 29 , 30 ] and makes it difficult to predict the long-term hearing outcomes of these patients. Possible undetected causes of USNHL in the pediatric population might be attributable to genetic variants of unknown/uncertain significance, undiagnosed congenital cytomegalovirus infection (as most cases are asymptomatic at birth), or asymptomatic/paucisymptomatic postnatal infections [ 5 , 10 , 12 ]. This study showed that the characteristics of UNSHL are highly variable regarding age at diagnosis, affected side, degree, hearing changes over time, audiometric configuration, and use of a hearing device.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of UHL increases with age; it is estimated that 7.2% of adults in the United States of America are affected by UHL [ 7 ]. The most common causes of unilateral sensorineural hearing loss (USNHL) include premature birth, congenital or postnatal infections (especially congenital cytomegalovirus and meningitis), structural anomalies (such as cochlear nerve hypoplasia/aplasia and enlarged vestibular aqueduct), genetic underpinnings, and temporal bone trauma [ 6 , 8 , 9 , 10 , 11 , 12 ]; however, in many cases, the etiology remains unknown [ 9 ]. A review by Lieu showed that UHL in children has a negative impact on speech–language development, cognition, and quality of life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%